PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MELATIHKAN SIKAP ILMIAH MATERI PEMANASAN GLOBAL KELAS VII SMP - Dian Masidayu Prahastuti; Nur Kuswanti; Andri Wahyu Wijayadi (Discovery, 2021)
Abstract: Based on questionnaires that have been distributed, it is known that the problem found in class VII SMP is a lack of interest in science subjects because the learning process is still a teacher-centered. Students are more interested in my practice-based learning. Referring to the results of the interview, it shows that one of the materials is with a low average value is Global Warming. In order to make it easier for educators to implement a learning system based on conditions and problems in the classroom, a learning device is needed that is in accordance with the conditions in the class. This study aims to develop a quality Guided Inquiry leson plan, as well as to explain the process of developing Guided Inquiry leson plan based on the ADDIE development procedure, and to describe the feasibility of the lesson plan developed based on the validity of the lesson plan. This research design uses ADDIE (Analyze, Design, Development, Implement, and Evaluate). The results of the validation of the validators obtained an average score of 4.7 and were categorized as very valid. So the lesson plan on global warming material based on guided inquiry learning models to train students' scientific attitudes is feasible to use in learning. Keywords: Global Warming, Guided Inquiry Model, Lesson Plan. Abstrak: Bersumber pada angket yang telah disebar diketahui bahwa masalah yang ditemukan pada kelas VII SMP adalah kurangnya minat pada mata pelajaran IPA dikarenakan proses pembelajaran yang masih bersifat teacher center, peserta didik lebih berminat pada pembelajaran yang berbasis praktiku. Jika mengacu pada hasil wawancara menunjukkan bahwa salah satu materi yang memiliki nilai rata-rata rendah adalah materi Pemanasan Global. Guna memudahkan pendidik mengimplementasikan sistem pembelajaran berdasarkan kondisi dan permasalahan di kelas maka dibutuhkan suatu perangkat pembelajaran yang sesuai dengan kondisi di kelas tersebut. Penelitian ini bertujuan untuk mengembangkan RPP Inkuiri Terbimbing yang berkualitas, serta untuk menjelaskan proses pengembangan RPP Inkuiri Terbimbing berdasarkan prosedur pengembangan ADDIE, dan mendeskripsikan kelayakan RPP yang dikembangkan berdasarkan validitas RPP. Desain penelitian ini menggunakan ADDIE (Analyze, Design, Development, Implement, dan Evaluate). Hasil validasi dari para validator, diperoleh rata-rata skor 4,7 dan dikatergorikan sangat valid. Jadi RPP pada materi pemanasan Global berbasis model pembelajaran inkuiri terbimbing untuk melatihkan sikap ilmiah peserta didik layak untuk digunakan dalam pembelajaran. Kata Kunci: Pemanasan Global, Model Inkuiri Terbimbing, RPP.